1996
DOI: 10.1038/sj.bdj.4808989
|View full text |Cite
|
Sign up to set email alerts
|

Fissure sealants: a 4-year clinical trial comparing an experimental glass polyalkenoate cement with a bis glycidyl methacrylate resin used as fissure sealants

Abstract: The 4-year results of a fissure sealant trial are reported. Glass polyalkenoate and bis GMA sealant were applied to 590 first permanent molar teeth using a half mouth study design in a group of 228 6-8-year-old children. Similar cariostasis was observed for the two materials at the end of 4 years despite marked differences in retention. Polyalkenoate cements probably should be regarded as 'fluoride depot' materials rather than fissure sealants when used in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 0 publications
5
54
1
3
Order By: Relevance
“…Eight trials (31)(32)(33)(34)(35)(36)(37)(38) and three literature review articles (2,11,12), were accepted and thus formed the basis for the evaluation of evidence regarding the caries-preventive effect of GIC versus that of resin-based fissure sealants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight trials (31)(32)(33)(34)(35)(36)(37)(38) and three literature review articles (2,11,12), were accepted and thus formed the basis for the evaluation of evidence regarding the caries-preventive effect of GIC versus that of resin-based fissure sealants.…”
Section: Resultsmentioning
confidence: 99%
“…Two trials (31,36) reported a fluoride concentration ranging from 0.1 to 0.7 ppm in the water supply. Five trials (32)(33)(34)(35)38) provided no information about the water fluoride concentration.…”
Section: Description Of Accepted Trialsmentioning
confidence: 99%
See 3 more Smart Citations